Pulsative hematoma: A penile fracture complication - Nale Đorđe; Mićić Sava (Vojnosanitetski Pregled)
Background. Fracture of the penis is a direct blunt trauma of the erect or semi-erect penis. It can be treated by conservative or surgical means. Retrospective analyses of conservative penile fracture treatment reveal frequent immediate and later complications. Case report. We presented a 41- year-old patient with pulsative hematoma caused by an unusual fracture of the penis. Fracture had appeared 40 days before the admittance during a sexual intercourse. The patient was treated surgically. Conclusion. Pulsative hematoma (pulsative diverticulum) is a very rare, early complication of a conservatively treated penile fracture. Surgical treatment has an advantage over surgical one, which was confirmed by our case report.